Insecticidal efficacy of afoxolaner against Stomoxys calcitrans (Diptera: Muscidae) in dogs - Eric Tielemans; Nesrine Aouiche; Adriaan Saunders; J.F. Besselaar; Frédéric Beugnet (Current Research in Parasitology and Vector-Borne Diseases, 2021)
The insecticidal activity of oral afoxolaner (NexGard®) against stable flies Stomoxys calcitrans (Diptera: Muscidae) that had fed on dogs was evaluated in a blinded, randomised, and negative controlled efficacy study. The efficacy assessments were based on survival rates of fed flies after challenges to treated dogs. For a challenge, each dog was exposed to 50 unfed S. calcitrans for 30 minutes, after which time live fed flies were collected and incubated in an insectarium for viability assessment after 48, 72 and 96 hours. Fourteen dogs were randomly allocated to an untreated control group and an afoxolaner-treated group of seven dogs each. NexGard® was administered on Day 0 per label instructions to the treated group. All dogs were challenged on Days 1, 7, 14, 21 and 28. Efficacy was calculated by comparison of the proportion of incubated live fed flies for each individual after their related 30-min challenges in the control and treated groups after 48, 72 and 96 hours of incubation. A significant afoxolaner activity against S. calcitrans was demonstrated, with efficacy at 96 hours after blood-feeding ranging from 76.4 to 98.5% through Day 28.